2002
DOI: 10.1023/a:1014697208218
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Mitral inflow velocities are widely used for the evaluation of left ventricular (LV) diastolic function. However, they are closely affected by other factors such as preload. The purpose of this study was to evaluate the usefulness of tissue Doppler velocities obtained from the mitral annulus for the evaluation of ventricular relaxation in patients under different loading conditions. We also evaluated the effect of preload at different sides on the mitral annulus. The study population consisted of 62 consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Tissue Doppler echocardiography (TDE) was found to be a new method to evaluate LV systolic and diastolic dysfunction [21]. Parameters derived from TDE were considered relatively preload-independent [22,23,24]. Some have reported that mitral annular velocity was preload-dependent especially in the early diastolic phase [25,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Tissue Doppler echocardiography (TDE) was found to be a new method to evaluate LV systolic and diastolic dysfunction [21]. Parameters derived from TDE were considered relatively preload-independent [22,23,24]. Some have reported that mitral annular velocity was preload-dependent especially in the early diastolic phase [25,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The time constant of relaxation τ is the gold standard parameter for the assessment of LV diastolic function, but it is not frequently used due to its invasive nature [3,4,5]. Echocardiography became the standard clinical tool for the noninvasive evaluation of LV diastolic function by measuring transmitral flow velocities obtained by the MPD technique [6,7,8].…”
Section: Discussionmentioning
confidence: 99%
“…However, for many instances, information obtained from MPD indices is inconclusive or contradictory. Furthermore, measurements obtained by MPD are load dependent, so patients with an abnormal relaxation and high left atrial pressure may have a normal MPD pattern called pseudonormalization [5,9,10,11, 18]. MPD is correlated with τ except when there is a pseudonormal filling pattern [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations